6000-year Chironomid record of composite sediment core SONK_11_D from Son Kol, Kyrgyzstan, Central Asia - Laug, Andreas (PANGAEA, 2019)
A 173.5 cm composite sediment core featuring the last 6000 years from the Central Asian lake Son Kol has been studied on its chironomid assemblages, showing two abrupt changes in species group composition.
Keywords: Central Asia; Chironomidae; Midges